PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR MATERI ORGAN PENCERNAAN MAKANAN MANUSIA SISWA KELAS V SEKOLAH DASAR - Utami, Petrisia Salsha Dyah Putri; Hakim, Lukman; Lefudin, Lefudin (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to determine the effect of the inquiry learning model on students' learning outcomes at SD Negeri 223 Palembang. The research applied an experimental design using a Nonequivalent Control Group Design. The population of this study consists of all fifth-grade students at SD Negeri 223 Palembang, the research samples are classes VA and VB. The instrument used is a multiple-choice test. The data analysis techniques employed include normality tests, homogeneity tests, and hypothesis testing. The results show that: (1) the average pretest score of the experimental class was 44.44, and the average posttest score was 69.13. In contrast, the average pretest score of the control class was 51.76, and the average posttest score was 64.77. (2) Based on the t-test results, the calculated value ttest is 46.58 and the table value ttable is 1.701, indicating that 46.58 > 1.701, which leads to the rejection of H0 and acceptance of Ha. Therefore, it can be concluded that the inquiry learning model has a significant effect on students' learning outcomes.